Efficacy of Stochastic Vestibular Stimulation to Improve Locomotor Performance During Adaptation to Visuomotor and Somatosensory Distortion - Temple, David R.; De Dios, Yiri E.; Layne, Charles S.; Bloomberg, Jacob J.; Mulavara, Ajitkumar P. (Frontiers in Physiology, 2018)
Astronauts exposed to microgravity face sensorimotor challenges affecting balance control when readapting to Earth’s gravity upon return from spaceflight. Small amounts of electrical noise applied to the vestibular system have been shown to improve balance control during standing and walking under discordant sensory conditions in healthy subjects, likely by enhancing information transfer through the phenomenon of stochastic resonance. The purpose of this study was to test the hypothesis that imperceptible levels of stochastic vestibular stimulation (SVS) could improve short-term adaptation to a locomotor task in a novel sensory discordant environment. Healthy subjects (14 males, 10 females, age = 28.7 ± 5.3 years, height = 167.2 ± 9.6 cm, weight = 71.0 ± 12.8 kg) were tested for perceptual thresholds to sinusoidal currents applied across the mastoids. Subjects were then randomly and blindly assigned to an SVS group receiving a 0-30 Hz Gaussian white noise electrical stimulus at 50% of their perceptual threshold (stim) or a control group receiving zero stimulation during Functional Mobility Tests (FMTs), nine trials of which were done under conditions of visual discordance (wearing up/down vision reversing goggles). Time to complete the course (TCC) was used to test the effect of SVS between the two groups across the trials. Adaptation rates from the normalized TCCs were also compared utilizing exponent values of power fit trendline equations. A one-tailed independent-samples t test indicated these adaptation rates were significantly faster in the stim group (n = 12) than the control (n = 12) group [t(16.18) = 2.00, p = 0.031]. When a secondary analysis was performed comparing “responders” (subjects who showed faster adaptation rates) of the stim (n = 7) group to the control group (n = 12), independent-samples t tests revealed significantly faster trial times for the last five trials with goggles in the stim group “responders” than the controls. The data suggests that SVS may be capable of improving short-term adaptation to a locomotion task done under sensory discordance in a group of responsive subjects.